Vertebrate-type intron-rich genes in the marine annelid platynereis dumerilii - Raible, Florian; Bork, Peer; Arendt, Detlev (Science, 2005)
Previous genome comparisons have suggested that one important trend in vertebrate evolution has been a sharp rise in intron abundance. By using genomic data and expressed sequence tags from the marine annelid Platynereis dumerilii, we provide direct evidence that about two-thirds of human introns predate the bilaterian radiation but were lost from insect and nematode genomes to a large extent. A comparison of coding exon sequences confirms the ancestral nature of Platynereis and human genes. Thus, the urbilaterian ancestor had complex, intron-rich genes that have been retained in Platynereis and human. Genes resembling intron-rich human genes are found in a marine polychaete, indicating their presence in the bilateral ancestor and their secondary loss in other invertebrates.
Gesehen am 17.05.2017